PENGARUH WAKTU MAKAN, STATUS GIZI, DAN ASUPAN ZAT GIZI TERHADAP KADAR ASAM URAT PADA VEGETARIAN DAN NON VEGETARIAN DI DESA PONIKI KECAMATAN PASAN MINAHASA TENGGARA - Irza Nanda Ranti; Stevina Y Barangmanise; Inka V. J. Tondatuon (Jurnal GIZIDO, 2017)
Uric acid is a normal metabolic waste of protein digestion or the end result of purine metabolism, both purine derived from food and purine derived from the breakdown of nucleic acid body. Vegetarians are people who do not consume meat or seafood or products that contain this type of food. The purpose of this research is to know the influence of meal time, nutritional status and nutrient intake in vegetarian and non vegetarian.The type of this research is descriptive observational analytic using design cross sectional. This study describes the effect of mealtimes, nutritional status and nutrient intake on uric acid levels in vegetarians and non-vegetarians. This research was conducted in Poniki Village of Pasan Minahasa Tenggara Sub-district from 1-7 May 2017. The sampling method is consecutive sampling with a total of 621 popolates with a sample of 35 vegetarians and 35 non-vegetarians and using a logistic regression test. The subjects of this study are all villagers of Poniki who meet the criteria.The results showed that the statistical test results using logistic regression test in the vegetarian group at step 6 variable lunch time has the value of expect = 0.167 which means lunch time is a variable that affect the increase in uric acid levels whereas in non-vegetarian groups have a value on The fifth step variable of nutritional status and protein intake have value of expect = 0.000, which means nutritional status and protein intake is variable that influence to increase uric acid level. In conclusion, the most influential variable in the vegetarian group is lunch time whereas in non-vegetarian group is the nutritional status and protein intake that most influence to increase uric acid level.